2003
DOI: 10.5194/acp-3-607-2003
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear relationships between atmospheric aerosol and its gaseous precursors: Analysis of long-term air quality monitoring data by means of neural networks

Abstract: Abstract. The nonlinear features of the relationships between concentrations of aerosol and volatile organic compounds (VOC) and nitrogen oxides (NO x ) in urban environments are revealed directly from data of long-term routine measurements of NO x , VOC, and total suspended particulate matter (PM). The main idea of the method is development of special empirical models based on artificial neural networks. These models, that are basically, the nonlinear extension of the commonly used linear statistical models p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…polytechnique.fr/chimere/. The tropospheric NO 2 column amounts simulated by CHIMERE were evaluated against the SCIAMACHY and GOME measurements in earlier studies (Konovalov et al, 2005;Blond et al, 2007). In this study, the model's domain covers all of Europe, the Mediterranean and the Middle East with a horizontal resolution of 1 • ×1…”
Section: Simulated Datamentioning
confidence: 99%
See 1 more Smart Citation
“…polytechnique.fr/chimere/. The tropospheric NO 2 column amounts simulated by CHIMERE were evaluated against the SCIAMACHY and GOME measurements in earlier studies (Konovalov et al, 2005;Blond et al, 2007). In this study, the model's domain covers all of Europe, the Mediterranean and the Middle East with a horizontal resolution of 1 • ×1…”
Section: Simulated Datamentioning
confidence: 99%
“…Neural networks are extensively used in air pollution studies for approximation of unknown relationships between the observed quantities and forecasting (see, e.g. Gardner and Dorling, 1998;Konovalov 2002Konovalov , 2003Lary et al, 2004;Hooyberghs, 2005;Argiriou, 2007;Feister et al, 2008). Second, we follow the Bayesian probabilistic approach, which is commonly used in inverse modeling and data assimilation studies and is applied here to the estimation of weight coefficients of the neural network.…”
Section: Description Of the Algorithmmentioning
confidence: 99%
“…Nitrogen oxides (NOx=NO+NO2) are important atmospheric constituents affecting climate processes and air quality specifically by serving as precursors of tropospheric ozone [1,2] and influencing secondary aerosol formation [3,4]. One of the significant sources of NOx on a global scale is associated with biomass burning (BB), including wildfires: it is estimated that biomass and biofuel burning provide around 15 % of NOx emissions globally [5].…”
Section: Introductionmentioning
confidence: 99%